Implementasi Spiritualitas Manajemen Keuangan dalam Pengelolaan Keuangan Biara Kongregasi PIJ Wairklau Maumere - Krispina Kara; Wilhelmina Mitan; Emilianus Eo Kutu Goo (Dharma Ekonomi, 2025)
This research is a case study describing the implementation of spirituality in financial management at the Wairklau Congregation Monastery of PIJ Maumere. The objective is to evaluate the application of the values of simplicity, transparency, and responsibility in financial management. The research utilized qualitative methods with an ethnographic approach, incorporating interviews, observations, and document reviews. The findings show that spirituality in financial management is effectively implemented in accordance with the established guidelines. Managers carry out their duties as a form of service, without expecting compensation, demonstrating a strong sense of spiritual commitment. One of the main challenges identified is maintaining effective communication within the team. This emphasizes the significance of managers who internalize spiritual values, enabling them to serve with integrity, responsibility, and accountability. Furthermore, it highlights the role of spirituality in fostering ethical behavior in financial practices. This research underscores the need for ongoing training and internalization of these values to enhance financial management effectiveness in religious institutions.